Polycystin-1, the PKD1 gene product, is in a complex containing E-cadherin and the catenins - Huan, Yonghong (American Society for Clinical Investigation, 1999)
Autosomal dominant polycystic kidney disease (ADPKD) is a common human genetic disease characterized by cyst formation in kidney tubules and other ductular epithelia. Cells lining the cysts have abnormalities in cell proliferation and cell polarity. The majority of ADPKD cases are caused by mutations in the PKD1 gene, which codes for polycystin-1, a large integral membrane protein of unknown function that is expressed on the plasma membrane of renal tubular epithelial cells in fetal kidneys. Because signaling from cell-cell and cell-matrix adhesion complexes regulates cell proliferation and polarity, we speculated that polycystin-1 might interact with these complexes. We show here that polycystin-1 colocalized with the cell adhesion molecules E-cadherin and α-, β-, and γ-catenin. Polycystin-1 coprecipitated with these proteins and comigrated with them on sucrose density gradients, but it did not colocalize, coprecipitate, or comigrate with focal adhesion kinase, a component of the focal adhesion. We conclude that polycystin-1 is in a complex containing E-cadherin and α-, β-, and γ-catenin. These observations raise the question of whether the defects in cell proliferation and cell polarity observed in ADPKD are mediated by E-cadherin or the catenins. J. Clin. Invest. 104:1459–1468 (1999).